2021
DOI: 10.31234/osf.io/ycmt4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncertainty makes me emotional: Uncertainty as an elicitor and modulator of emotional states

Abstract: Uncertainty and emotion are an inevitable part of everyday life and play a vital role in mental health. Yet, our understanding of how uncertainty and emotion interact is limited. Here, an online survey was conducted (n = 231) to examine whether uncertainty evokes and modulates a range of negative and positive emotions. The data show that uncertainty is predominantly associated with negative emotional states such as fear/anxiety. However, uncertainty was also found to modulate a variety of other negative (i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Feelings of uncertainty, evoked in contexts that are unfamiliar, ambiguous, or depart from expectations, are associated with negative emotional states, particularly fear/anxiety but also with other negative emotions, including being upset, angry, frustrated, sad or confused (see Morriss et al, 2022 ). Consistent with the emotion eliciting nature of Novel contexts, the temperament variables entered in the path model explained more variance in ARC in the Novel (41%) than the Routine context (17%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feelings of uncertainty, evoked in contexts that are unfamiliar, ambiguous, or depart from expectations, are associated with negative emotional states, particularly fear/anxiety but also with other negative emotions, including being upset, angry, frustrated, sad or confused (see Morriss et al, 2022 ). Consistent with the emotion eliciting nature of Novel contexts, the temperament variables entered in the path model explained more variance in ARC in the Novel (41%) than the Routine context (17%).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-schoolers often encounter new experiences that ordinarily become routine over time and face unanticipated departures from routines or expectations. Uncertainties inherent in unfamiliar or unexpectedly changing situations increase feelings of fear or discomfort ( Morriss et al, 2022 ), particularly in individuals who are prone to higher NA reactivity, and may also heighten other negative emotions such as sadness or anger ( Bar-Anan et al, 2009 ). Hence, the disruptive effects of NA on functioning are particularly apparent in the face of novelty or departures from expectations ( Kagan, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current theoretical models and a wealth of empirical research suggests that uncertainty is aversive in and of itself, and thus engages the behavioural inhibition system (Gray, 1976) responsible for negative emotional states such as fear and anxiety (Brosschot et al, 2016;Carleton, 2016;Grupe & Nitschke, 2013;Hirsh et al, 2012). Alongside this literature, however, there is also an emerging body of empirical research suggesting that uncertainty may evoke and modulate other negative and positive emotional states as well (Bar-Anan et al, 2009;Fontaine et al, 2007;Morriss et al, 2019;Morriss, Tupitsa, et al, 2022;Van Dijk & Zeelenberg, 2006). For instance, in a recent online survey study, found that different parameters of uncertainty (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…happiness/joy and, excitement/enthusiasm), emotional states respectively. Despite progress in understanding how uncertainty and emotion intersect (Anderson et al, 2019;Fontaine et al, 2007;Morriss, Tupitsa, et al, 2022;Roseman, 1984;Smith & Ellsworth, 1985), very little is understood as to how individual differences contribute to uncertainty and emotion interactions (Anderson et al, 2019;Hillen et al, 2017). A growing body of research has started to highlight how the transdiagnostic risk factor, Intolerance of Uncertainty (IU), the tendency to view uncertainty as unbearable and stressful (Carleton et al, 2007;Freeston et al, 1994), is associated with greater experience of negative emotional states such as fear and anxiety (Morriss, Wake, et al, 2021;Morriss, Zuj, et al, 2021;Tanovic et al, 2018).…”
Section: Introductionmentioning
confidence: 99%